Young microglia restore amyloid plaque clearance of aged microglia. (21st December 2016) - Daria, Anna; Colombo, Alessio; Llovera, Gemma; Hampel, Heike; Willem, Michael; Liesz, Arthur; Haass, Christian; Tahirovic, Sabina
Abstract: Alzheimer′s disease (AD) is characterized by deposition of amyloid plaques, neurofibrillary tangles, and neuroinflammation. In order to study microglial contribution to amyloid plaque phagocytosis, we developed a novel ex vivo model by co‐culturing organotypic brain slices from up to 20‐month‐old, amyloid‐bearing AD mouse model (APPPS1) and young, neonatal wild‐type (WT) mice. Surprisingly, co‐culturing resulted in proliferation, recruitment, and clustering of old microglial cells around amyloid plaques and clearance of the plaque halo. Depletion of either old or young microglial cells prevented amyloid plaque clearance, indicating a synergistic effect of both populations. Exposing old microglial cells to conditioned media of young microglia or addition of granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) was sufficient to induce microglial proliferation and reduce amyloid plaque size. Our data suggest that microglial dysfunction in AD may be reversible and their phagocytic ability can be modulated to limit amyloid accumulation. This novel ex vivo model provides a valuable system for identification, screening, and testing of compounds aimed to therapeutically reinforce microglial phagocytosis. Synopsis: Phagocytic function of aged microglial cells in amyloid plaque‐bearing tissue is not irreversibly impaired, but can be restored through factors secreted by young microglia. Microglia function in Aβ clearance and reducing the amyloid burden highlights the need for development of therapeutic approaches modulating microglial activity. A novel ex vivo co‐culture model for amyloid plaque clearance by microglia is established. Enhanced amyloid clearance and reduced plaque size occurs upon co‐culturing young WT and old APPPS1 brain slices or exposure of old microglia to conditioned media of young microglia or GM‐CSF. Factors secreted by young microglia stimulate proliferation of old microglia, which is a pre‐requisite for enhanced clearance of the plaque halo. Abstract : Impaired phagocytic function of aged microglia can be rescued via GM‐CSF secretion from co‐cultured young microglia in amyloid‐bearing organotypic tissue.